Characteristics of Rural Architecture and its use in the çomakdaĞ Region: çomakdaĞ KizilaĞaç Village, Turkey - V. Betül Kurtuluş; Neriman Şahin Güçhan (Taylor & Francis Group, Vernacular Architecture, 2020)
Çomakdağ is a rural region consisting of five villages and six plateau settlements in the Beşparmak mountain range in Milas district, Muğla province, Turkey. The simple stone masonry buildings on the rocky cliffs and the indigenous lifestyle of the local people form unique characteristics of the region. The historic urban fabric is still visible, and the traditional lifestyle continues in the region. However, the population has been decreasing, and some parts of the traditional fabric have lost their local characteristics. This article presents the typical characteristic of the Çomakdağ houses that date from the late nineteenth and twentieth centuries. The aim is to introduce the rural architecture of the region and investigate the interactions between spaces and daily life. Moreover, physical interventions to adapt the houses to today’s needs in the Çomakdağ Kızılağaç village are explored through observations and interviews.
Keywords: Çomakdağ; Çomakdağ Kızılağaç village; rural architecture; daily life; user interventions